Quality characteristics and hatchability of eggs and serum electrolytes concentration of Gola, Giribaz and Ghiachundi pigeon breed - Sujan, Khaled Mahmud; Biswas, Manik; Tareq, Sakhawat Hossain; Islam, Md Kamrul (Asian Journal of Medical and Biological Research, 2021)
The weather and vast areas of crop fields along with housing premises of Bangladesh are suitable for pigeon farming. The experiment was conducted to evaluate the characteristics of eggs and serum electrolyte concentration of Gola, Giribaz and Ghiachundi pigeon squabs. Three pairs of each breed were reared in the cage with commercial feed and water. After laying eggs, the length and width of eggs were recorded. After hatching of eggs, eggshell thickness was recorded. The thickness of the eggshell was 0.15±0.01 mm, 0.15±0.01 mm, 0.15±0.00 mm for Gola, Giribaz and Ghiachundi breeds respectively. The body weights of the squabs were recorded at 7th and 45th day. The squabs were sacrificed on 45th day and the blood sample was collected and serum sodium, potassium, calcium and phosphorus concentration were measured by using appropriate analytical techniques. Serum sodium, potassium, calcium and phosphorus were: 102.93±15.95 (mmol/L), 11.18±2.19 (mmol/L), 6.20±1.11 (mmol/L), 4.53±0.45 (mmol/L) for Gola breed; 101.48±2.12 (mmol/L), 12.15±0.96 (mmol/L), 5.65±1.09 (mmol/L), 4.53±0.36 (mmol/L) for Giribaz breed and 95.18±6.71 (mmol/L), 11.99±0.91 (mmol/L), 5.09±0.75(mmol/L), 4.81±0.24 (mmol/L) for Ghiachundi breed respectively. A positive correlation has been found between thickness of eggshell and phosphorus while there is a negative correlation with calcium for Gola breed; both have been found insignificant for Giribaz breed and only calcium has been found significant for Ghiachundi breed. A strong correlation between the final body weight of the squab and K for the Gola breed; between the final body weight of the squab and Ca, P, K for Giribaz breed and between the final body weight of the squab and Ca, Na, K have been found. It could be concluded that serum electrolytes having an influential effect on egg characteristics and body weight of corresponding pigeon breed. Asian J. Med. Biol. Res. 2021, 7 (2), 107-112